The Contradiction of Meaning in Building Sympathy for Puan Maharani (A Semiotics Analysis of Puan Maharani’s Clothing Giveaway Video in Bekasi) - Siwi, Yogi Raka; Sadono, Teguh Priyo (Interaction Communication Studies Journal, 2025)
This research examines the public figure Puan Maharani in the context of her efforts to cultivate public sympathy. The study focuses on a video in which Puan Maharani is seen distributing clothing to residents in Bekasi, revealing a significant contradiction between her symbolic actions and the nonverbal expressions she displays. To analyze this phenomenon, the study employs Relational Dialectics Theory as proposed by Leslie Baxter, alongside a semiotic approach developed by Roland Barthes, which explores three levels of meaning: denotation, connotation, and myth. The findings suggest that actions intended to generate public sympathy instead provoked sarcastic reactions and public criticism. This indicates that in the realm of communication, it is not only the content of the message that holds significance, but also the manner of its delivery and the accompanying symbolic gestures.